DETERMINANT ANALYSIS OF INDONESIAN GDP PER CAPITA 1991-2020: ECM METHOD - Rekno Hidayati; Lucia Rita Indrawati (Transpublika Publisher, 2022)
Indonesia's economic growth is known to fluctuate. The government and banks have taken a number of policies to maintain macroeconomic stability that have an impact on the domestic economy in order to prevent a recession from occurring on economic growth. This study aims to determine the factors that can affect GDP per capita in the long term and short term. This study uses descriptive and quantitative methods, and the methodology used is econometrics and processed using statistical software EVIEWS. In this study, the data used is secondary data in the form of time series or time series. The variables tested include Final Consumption Expenditure, Foreign Investment, and the Female Labor Participation Rate. The results of the analysis on short-term tests, all variables tested have no significant effect on GDP per capita. Meanwhile, in the long run it is known that only the final consumption expenditure variable has an effect on Indonesia's GDP per capita for the 1991-2020 period.